Contesting medical treatment: Lead-pollution and the Karen of Klity Creek (Kanchanaburi, Thailand) - Malee Sitthikriengkrai (2018)
© 2018 Editions Saint-Paul. All rights reserved. Since the mid-1970s the forested area of Klity Creek, northwest of Bangkok, suffered from one of the worst cases of industrial pollution in Thailand caused by a floating lead mine that operated in the area. Toxic waste found its way into the stream, used for daily food and water consumption by the local (Pwo-) speaking Karen villagers. After an NGO came to their aid, introducing the Karen villagers to the environmental justice movement of Thailand, the villagers came to seek redress. They demanded pharmacological intervention from the Ministry of Public Health. The intervention they received was "health surveillance," which led them to reject the treatment offered. This article focuses on the protest as well as the gap between medical intervention and the experiential needs of people suffering from environmental illness as well as the role of civic activism in framing the issue of illness.